Multivariate VaRs for operational risk capital computation: a vine structure approach. (1st January 2013) - Guégan, Dominique; Hassani, Bertrand K.
The Basel advanced measurement approach requires financial institutions to compute capital requirements on internal datasets. In this paper, we introduce a new methodology permitting capital requirements to take into account the embedded dependence structures of operational risks. The loss distributions are provided in a matrix of 56 cells. Constructing a vine architecture, which is a bivariate decomposition of a n -dimensional structure ( n > 2), we use this approach to compute multivariate operational risk VaRs. We analyse the results and compare them with classical methodologies based on LDF modellings. Our method is simple to carry out, easy to interpret and complies with the new Basel Committee requirements.